Ice Nucleation Measurement and Parameterizations and the Broad Impact of Associated Ocean and Atmospheric Interactions Within the Global Climate ... - Unkn Unknown (University of Wyoming. Libraries, 2024)
Current climate models attempt to represent the frequency and characteristics of mixed-phase and ice clouds in the atmosphere. Ice crystals have the ability to scatter incoming solar radiation, which may have a net cooling effect on the Earth’s energy budget. Ice forms in the atmospheric by either homogenous freezing at temperatures colder than -36°C, or by heterogeneous freezing, which requires an ice nucleating particle (INP) to initiate freezing at temperatures warmer than -36°C. The stochastic nature of ice formation requires more rigorous development and testing of model parameterizations that aim to predict ice formation. In this study, we have measured the immersion freezing temperatures of sea surface microlayer (SML) samples collected in the North Atlantic Ocean and used our results to examine the accuracy of a global ice nucleation parameterization to predict marine INP concentrations. SML samples from the fourth NASA North Atlantic Aerosol and Marine Ecosystem Study (NAAMES4) field campaign were ...